Prophylactic Negative Pressure Wound Therapy in Reducing Surgical Site Infections: An Evidence-Based Literature Review - Marika Formosa BSc (Hons); Stephen J. Ebejer PhD, MSc, MA, BSc (Hons) (SAGE Publishing, 2024)
Background Surgical site infections (SSIs) are a frequent postoperative complication that nurses commonly need to provide asepsis-specific meticulous care for. The application of a closed-incisional negative pressure wound therapy (iNPWT) device is regarded as a novel technique that aims to lower the risk of external wound contamination. Aim The purpose of this review was to evaluate the effectiveness of iNPWT on high-risk closed laparotomy incisions with the aim to inform nursing practitioners and physicians engaged in multieffort wound care practices. Nursing professionals play a crucial role in mitigating the incidence of SSIs, from the time of application, through ongoing assessment tissue condition, and ensuring asepsis, thereby enhancing patient care and safety. The Research Question Is prophylactic negative pressure wound therapy effective in reducing the incidence of (closed) surgical site wound infections postlaparotomy? PICO Elements The population studied included patients undergoing laparotomy surgery. The intervention under review included the application of iNPWT, compared to the use of standard gauze dressing. The expected outcome was SSI reduction. Methods and Results A systematized literature search was conducted using various databases to identify published studies that address the PICO question. The PRISMA checklist and Critical Appraisal Skills Programme tools allowed to exclude irrelevant articles and to critically appraise the evidence, respectively. Eleven key articles were retrieved including four RCTs and seven systematic reviews and meta-analysis. The results indicated an overall positive association between iNPWT and a reduction in SSI in laparotomy surgeries when compared to standard dressings. Linking Evidence to Action Data across most studies reviewed support the benefits with the use of iNPWT as a preventive strategy to lower the rates of SSI, with some claiming no difference. Although heterogeneity in the studies precludes a definite conclusion, nurses may make a more informed decision when navigating the demands of SSI prevention targeted nursing care.